Temporal trends of splenectomy in pediatric hospitalizations with immune thrombocytopenia. Issue 7 (10th April 2018) - Bhatt, Neel S.; Bhatt, Parth; Donda, Keyur; Dapaah‐Siakwan, Fredrick; Chaudhari, Riddhi; Linga, Vijay Gandhi; Patel, Bhumi; Lekshminarayanan, Anusha; Bhaskaran, Smita; Zaid‐Kaylani, Samer; Badawy, Sherif M.
Abstract: Background: Splenectomy is considered an effective treatment for immune thrombocytopenia (ITP) with 70–80% response rate. However, its current use is limited in children with ITP. It is unclear if the rates of splenectomy have changed over time. Using a large nationally representative database, we aimed to study the trends of splenectomy in pediatric hospitalizations with ITP, and the factors associated with splenectomy during these encounters. Methods: Using National (Nationwide) Inpatient Sample (NIS), and international classification of diseases (9th revision), clinical modification (ICD‐9‐CM) codes, we studied pediatric ITP hospitalizations with occurrence of total splenectomy between 2005 and 2014. Results: Out of 37, 844 weighted ITP hospitalizations from 2005 to 2014; total splenectomy was performed in 954 encounters. Splenectomy rate declined over time (3.4% [2005–2006] to 1.6% [2013–2014], P < 0.001) with the younger age (≤5 years) having the most notable decline (0.91% [2005–2006] to 0.14% [2013–2014], P < 0.001). Splenectomy had higher odds of being performed electively than non‐electively (odds ratio [OR]: 19.34, 95% confidence interval [CI]: 12.06–31.02, P < 0.001). Encounters with intracranial bleed were associated with the occurrence of splenectomy (OR: 17.87, 95% CI: 5.07–62.97, P < 0.001). Intracranial bleed ( P < 0.001), gastrointestinal bleed ( P < 0.01), sepsis ( P < 0.001), and thrombosis ( P < 0.001) were associated with longer length of stay and higher cost of hospitalization. Conclusions: Overall, splenectomy rates consistently declined over time. Intracranial hemorrhage during hospitalizations with ITP was associated with occurrence of splenectomy. Future studies should continue to reevaluate the rates of splenectomy in pediatric ITP in the presence of various second‐line pharmacologic agents.